Evaluation of Enterobacter sp. strain G87 as potential probiont against Vibrio harveyi infection in Artemia nauplii and Asian seabass (Lates calcarifer) larvae - Zakaria, Zeti Hafiza; Mohd Yaminudin, Nur Jasmin; Md Yasin, Ina Salwany; Mohd Ikhsan, Natrah Fatin; Abd Karim, Murni Marlina (Universiti Putra Malaysia Press, 2019)
Probiotic has gained many interests as an alternative method in preventing and treating diseases in aquaculture. The benefits include improving feed value, inhibition of pathogenic microorganisms, anti-mutagenic and anti-carcinogenic activity, growth promoting factors, and increase host immune response. This research was carried out in order to evaluate the potential of probiont Enterobacter sp. G87 in conferring protection to Artemia and seabass larvae against Vibrio harveyi infection. In preliminary in vivo test, Artemia nauplii was treated with Enterobacter sp. G87 at three different concentrations 104, 106 and 108 CFU mL-1 and challenged with V. harveyi at 105 CFU mL-1. After challenged, significant increased survival was found in Artemia (78±2%) treated with 106 CFU mL-1 of Enterobacter sp. G87 compared with challenged group with no probiont added (48±2%). From the results, two concentrations of probiont (106 and 108 CFU mL-1) were selected to be used in seabass larvae in vivo challenge assay. After challenged with V. harveyi at 105 CFU mL-1 highest survival was found in seabass larvae treated with 106 CFU mL-1 of Enterobacter sp. G87 (95±3%). Additionally, Enterobacter sp. G87 was also able to reduce Vibrio counts both in Artemia and seabass larvae culture. This study showed that probiont Enterobacter sp. G87 was able to protect Artemia nauplii and seabass larvae from Vibrio harveyi infection and has a potential to be further studied in a larger scale.